محافظ تمام تنه با فشار منفي حين لوله گذاري تراشه و لاپاراسكپي در دوران همه گيري COVID19 - نارتینیان, آرتور; سلیمی, علیرضا; امین نژاد, رضا; صفری, سعید; باستان حق, احسان (مجله انجمن آنستزیولوژی و مراقبت‌های ویژه ایران, 2020)
During coronavirus disease 2019 (COVID-19) and the need to continue surgeries in the operating rooms, it is necessary to pay attention to protection of health care workers in daily practice. Aerosol-generating procedures like tracheal intubation and laparoscopic surgery is subject to challenge to find ways beyond the personnel protection equipment (PPE). In this letter we are introducing a concept that is full body light plastic cover with negative pressure for the tracheal intubation time until the end of laparoscopic surgery, that is light, portable, reusable and not cumbersome at all.